BEBERAPA HAMBATAN YANG DIHADAPI HAKIM DALAM PROSES PEMERIKSAAN PERKARA PIDANA KORUPSI DI PENGADILAN NEGERI JAMBI - , Islah (Jurnal LEX SPECIALIS, 2010)
Abstract Judges are required to be fair in deciding a case that they handle this certainly is not easy while the judge meet some obstacles in the process dropped the verdict against the defendant, prior to the defendant's criminal corruption case, there are who think this happened because of political factors, material factors and other things. Of course this gives a bad image of judges and court institutions, so as not to arise to know what the negative impact of these barriers.